The Effect of Temperature and Weather Conditions on the Performance of Photovoltaic Modules in Tropical Indonesia - ZM, Ajub Ajulian; Sinuraya, Enda Wista; Winardi, Bambang (Westscience Press, 2025)
This study explores the effect of temperature and weather conditions on the performance of photovoltaic (PV) modules in tropical Indonesia, utilizing a qualitative approach with interviews from five solar energy professionals. The research identifies key environmental factors such as high temperatures, humidity, and rainfall as significant influences on PV module efficiency. Participants noted that elevated temperatures reduce energy output by causing thermal losses, while high humidity and rainfall lead to dust accumulation and reduced sunlight exposure, further affecting efficiency. Additionally, challenges related to corrosion and dust accumulation were highlighted, particularly in coastal and inland regions. The study also suggests various strategies, including the use of anti-reflective coatings, cooling systems, and optimal panel placement, to mitigate these effects. Regional variations in climate necessitate site-specific maintenance and design strategies. This research provides important insights into optimizing PV system performance in tropical climates and emphasizes the need for tailored approaches in PV design and maintenance.